Decellularized spleen matrix for reengineering functional hepatic-like tissue based on bone marrow mesenchymal stem cells. (2nd July 2016) - Xiang, Junxi; Zheng, Xinglong; Liu, Peng; Yang, Lifei; Dong, Dinghui; Wu, Wanquan; Liu, Xuemin; Li, Jianhui; Lv, Yi
ABSTRACT: Background and Aims : Decellularized liver matrix (DLM) hold great potential for reconstructing functional hepatic-like tissue (HLT) based on reseeding of hepatocytes or stem cells, but the shortage of liver donors is still an obstacle for potential application. Therefore, an appropriate alternative scaffold is needed to expand the donor pool. In this study, we explored the effectiveness of decellularized spleen matrix (DSM) for culturing of bone marrow mesenchymal stem cells (BMSCs), and promoting differentiation into hepatic-like cells. Methods : Rats' spleen were harvested for DSM preparation by freezing/thawing and perfusion procedure. Then the mesenchymal stem cells derived from rat bone marrow were reseeded into DSM for dynamic culture and hepatic differentiation by a defined induction protocol. Results : The research found that DSM preserved a 3-dimensional porous architecture, with native extracellular matrix and vascular network which was similar to DLM. The reseeded BMSCs in DSM differentiated into functional hepatocyte-like cells, evidenced by cytomorphology change, expression of hepatic-associated genes and protein markers, glycogen storage, and indocyanine green uptake. The albumin production (2.74±0.42 vs . 2.07±0.28 pg/cell/day) and urea concentration (75.92±15.64 vs . 52.07±11.46 pg/cell/day) in DSM group were remarkably higher than tissue culture flasks (TCF) group over the same differentiation period, P < 0.05. Conclusion : This present study demonstrated that DSM might have considerable potential in fabricating hepatic-like tissue, particularly because it can facilitate hepatic differentiation of BMSCs which exhibited higher level and more stable functions.